Single phase induction motor studies using MATLAB / Izmir Mohd Yatim - Mohd Yatim, Izmir (2007)
An induction machine is a robust and very widely used industrial machine. As the load varies, the characteristics of the machine will also vary. From this project, we will learn more about these characteristics by using MATLAB software. Simulation of a single phase induction machine will be performed by M-File programming and Simulink. From these simulations, we can study the relationships of the motor such as their torque, slip, line current, frequency and the voltage and current waveforms across the motor.